2021
DOI: 10.2478/adms-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Analysis of the Influence of the Flux-Cored Wire Chemical Composition on the Electrical Parameters and Quality in the Underwater Wet Cutting

Abstract: The paper presents research in the field of underwater wet cutting with the use of flux-cored wires in order to improve the quality and performance. The research has resulted into the development of gas and slag systems for flux-cored wires and determination of, optimal parameters for cutting stability and quality. The underwater wet cutting mechanism is a cyclical process with the formation of periodic keyholes in metal, and it consists of operating and idle cycles. Efficiency of the cutting process can be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Many studies constantly appear to suggest new methods for the improvement in stability and quality of underwater wet welding [ 6 , 7 , 8 ]. The work of Surojo et al (2020) reported that underwater welding related to high risks for welders, such as electric shock.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies constantly appear to suggest new methods for the improvement in stability and quality of underwater wet welding [ 6 , 7 , 8 ]. The work of Surojo et al (2020) reported that underwater welding related to high risks for welders, such as electric shock.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the quality of cutting, Parshin have provided a criterion based on the ratio of the voltage probability density in the idle and operating cycles. (Parshin et al, 2021c) However, the arc sensor was not able to monitor the cutting process or to detect the cutting depth as the arc would go out when the cut bottom declined. Underwater vision sensor is important but must overcome the challenge of water turbidity and bubbles fluctuation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the specific environment, many structures, including offshore structures (such as oil and gas platforms, wind farms, ports, hydraulic structures, subsea oil and gas pipelines) need to be repaired, and components to be scrapped or reconditioned, so underwater cutting work is being carried out [26]. An exemplary study on this topic was published by Parshin et al [27,28]. They present a study on underwater wet cutting with the use of flux-cored wires to improve quality and performance.…”
Section: Introductionmentioning
confidence: 99%